(untitled) (Altre Modernità, 2015)
This paper aims to explore the artistic biography of Ida Kaminska – the leading figure of the Yiddish theatre in Poland in the 20th century – proposing a new metaphor for the theatrical experience of the Ashkenazi Jews and a different use of the audio-visual sources. First, I will explain why we can look at the Yiddish theatre as a house (heym) with a lot of windows, then I will examine Kaminska’s performance in three different films – On a heym (Without a Home, 1939), Obchod na korze (The Shop on Main Street, 1965) and The Angel Levine (1970) – through this peculiar metaphor. Even if they are not recordings of the theatrical performance, these documents could help us to understand some of the features of Kaminska’s art (i.e., the focus on identity, otherness and Yiddish language) and how they changed after the Holocaust.